THE IMPACT OF TOURIST’S SOCIO-DEMOGRAPHICS ON THE CHOICE OF ALCOHOL AND CHOICE OF DRINKSCAPES - Dsouza, Edgar Philip; M.S, Dayanand; Borde, Nilesh (Revista de turism - studii și cercetări în turism, 2021)
The present paper reveals the results of a study undertaken with the tourist visiting Goa in the tourist season from December 2020 to March 2021, yielding 962 valid responses. The study's objective was to analyze the impact of socio-demographic profiles of a tourist on the choice of alcohol, choice of drinkscapes and consumption patterns. Results point at a clear distinction between a wealthier, older group of tourists and gender contrasting with a lesser income and younger respondents with regards to the choice of alcohol and choice of drinkscapes. The findings may aid in understanding the alcohol consumption patterns of tourists and assist in better target marketing to each group while also comprehending the actual and prospective role of each group for beverage tourism.